Faktor-Faktor Yang Mempengaruhi Interaksi Sosial Pada Anak Usia Dini: Literatur Review - Batinah Batinah; Arum Meiranny; Atika Zahria Arisanti (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
One form of early adolescence development is the ability to have interaction socially, social development can be affected if the kid's potential to take social roles makes children aware of the mind, feelings, and attitudes of others. the kid's high-quality or terrible self-image is encouraged if the kid is a success or not inside the affiliation. the kid's capacity to conform to the environment, acceptance of the surroundings and other high-quality reviews for the duration of social sports is a completely vital fundamental capital. Literature review aims to look at the related factors that have an effect on social interplay in early adolescence. In writing this newsletter, the method used was a overview of literature opinions contained in the database of health journals, particularly Google student and Pubmed, selected articles primarily based on complete textual content, unfastened open get admission to, in English and in Indonesian. Writing literature through the writer's database determined 16 articles thru Google student and four articles via PubMed. After the assessment was performed, there were 8 appropriate journals. The effects acquired were factors that have an effect on the capacity of interaction in kids, particularly: parenting, environment, gambling with friends and the usage of devices. Keywords: Interaction influence factors, Social interaction ability, Early childhood.